Pedagogical Projecting of the Model of a Future Specialist - Oleksandr Mozolev (Педагогічний дискурс)
Training future specialist to professional activity is one of the main tasks of higher and professional education. Pedagogical modeling of professional activity is used to determine the content of quantitative and qualitative information, which is necessary for modern researchers to further work, and also directs them to the prospects of career growth.